Antimicrobial Activity of Warbugia Ugandensis against Gramnegative Multi‐Drug resistant Bacteria - Budambula, N. L. M. (Jomo Kenyatta University of Agriculture and Technology, 2014)
The rise in antibiotic resistance has resulted in decreasing numbers of effective antimicrobial agents available to treat infections caused by multi‐drug resistant (MDR) bacteria. This has necessitated a search for new antimicrobial agents. Herbal remedies may offer alternative treatment options especially because they elicit little or no transferable resistance if used in optimal concentrations. This study evaluated the antimicrobial properties of W. ugandensis against eight multi drug resistant (MDR) Gram‐negative bacterial isolates. The herbal extracts were obtained using methanol as an organic solvent and water as an inorganic solvent. Determination of the Minimum Inhibitory Concentrations (MICs) and the sub‐lethal concentrations of the effective extracts was done using broth inoculation method followed by colony count. The test isolates were habituated in sub‐lethal extract concentrations (SLC) for 72 h to investigate effect on their sensitivity to conventional antibiotics. Methanol extracts from the root and stem‐bark of W. ugandensis were active against the test strains and their inhibitory effect was significantly different (p<0.05) from that of other extracts. We determined that the extracts had an inhibitory rather than a lytic (cidal) mode of action. The extracts from this plant had an effective MIC of 42 μg/ml and exhibited an inhibitory mode of action and did not elicit resistance to conventional antibiotics. Methanol extracts from the root and bark of this plant may provide potential sources for further development of alternative antimicrobial agents for the treatment of MDR infections.
Keywords: multi‐drug resistant (MDR) bacteria; minimum inhibitory concentrations (MICs); sub‐lethal concentration (SLC)